COMPENSATION OF REACTIVE POWER THROUGH AUTOMATIC CONTROL OF CAPACITOR BATTERIES IN TEXTILE ENTERPRISES - Zokhidov Iqboljon Zokirjonovich; Tuxtashev Alisher Akmaljon ugli; Eshquziev Khurshidjon Musajonovich (American Journals Publishing, 2023)
It is known that today the number of industrial enterprises is increasing and the majority of energy consumers in them are the main part of the demand for asynchronous motors and valve transformers used in automated systems. The increase in the demand for reactive power has a negative effect on the indicators of the quality of electricity. Considers the problem of selecting reactive power compensation devices in distribution networks. Today, ensuring the quality of electricity is a very important task. One of the ways to achieve electricity parameters from consumers that meet the regulatory requirements is to install reactive power compensation in the network.
Keywords: Textile enterprises, reactive power, quality indicators, compensation, capacitor batteries, power factor, PFR-12